Regeneration of Chitosan-Based Adsorbents for Eliminating Dyes from Aqueous Solutions. Issue 1 (2nd January 2019) - Vakili, Mohammadtaghi; Deng, Shubo; Shen, Lu; Shan, Danna; Liu, Dengchao; Yu, Gang
Abstract : Chitosan and its derivatives are effective for adsorbing dye molecules from aqueous solutions. However, their use can be limited by environmental concerns on their fate after adsorbent saturation. Desorbing dye molecules and regenerating adsorbents are alternatives to disposing spent adsorbent. In this review, most research topics related to regenerating chitosan-based adsorbents for dye removal are summarized and discussed. Numerous desorption agents, such as acids, alkalis, salts, and organic solvents, have been applied to regenerate chitosan-based adsorbents and recover the adsorbed dye molecules. In addition, the mechanism of desorbing dye molecules from these adsorbents is examined to provide information on selecting methods for recovering chitosan-based adsorbents.